Application of Project Based Learning (PBL) Method to Improve Learning Outcomes of The Material on Cultivating Good Morals In Neighboring And Society Life For Students Of MIS Miftahul Huda Bajulan Village, Saradan District, Madiun Regency - Yusro; Newis, Yumma; Indrawan, Yuni; Mutaqin, Zaenal; Sinaga, Yusmarida (Jurnal Cendekia Islam Indonesia, 2025)
This study aims to analyze the application of the Project Based Learning (PBL) method in improving learning outcomes on the material of Cultivating Good Morals in Neighborhood and Community Life at MIS Miftahul Huda, Bajulan Village, Saradan District, Madiun Regency. The research method used is classroom action research (CAR) with a qualitative and quantitative approach. The subjects of the study were MIS Miftahul Huda students who participated in learning with the PBL method. Data were collected through observation, interviews, learning outcome tests, and documentation. The results showed that the application of the PBL method significantly improved students' understanding of the material, social skills, and their attitudes in interacting with the community. With project-based learning, students are more active in understanding the concept of good morals and applying them in everyday life. In addition, this method also encourages students to work together, think critically, and increase their sense of responsibility in their social environment. Based on these findings, the PBL method can be used as an effective learning strategy in moral education, because it provides a more contextual and applicable learning experience. Thus, PBL contributes to forming better student characters in interacting with their social environment.